PENGARUH AROMATERAPI LAVENDER TERHADAP TINGKAT NYERI PERSALINAN KALA 1 FASE AKTIF PADA IBU PRIMIGRAVIDA DI WILAYAH KERJA PUSKESMAS SEI LANGKAI BATAM TAHUN 2018 - L Tobing, Viona Kristo; Sihombing, Sarmauli Franshisca (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2018)
Pain is an unpleasant sensory and emotional experience due to actual and potential tissue damage. The second highest maternal birth rate is at PUSKESMAS SeiLangkai, namely 3256 people. The aim of the study was to determine the effect of lavender aromatherapy on the levels of labor pain atPuskesmasSeiLangkai working Area, Batam. This study was conducted in June-July, with all mothers giving birth and Accidental sampling. The research design was pre-test post-test with experimental research method. Data analysis using the T-test which previously tested the Kolmogrov Smirnov Normality. The results showed that there was a reduction of 0.4 with a p-value of 0.000 (p <0.05). Labor Pain Level before being given Aromatherapy Lavender obtained the majority of severe pain 17 respondents (56.7%) and after being given Aromatherapy Lavender became moderate pain 18 respondents (60%). Hence, it can be concluded that there is an effect of Lavender Aromatherapy on the level of labor pain in Puskesmas SeiLangkai working area, Batam. It is suggested for research site as one of the inputs for health workers (midwives) are always updated regarding pain management so that they can provide care for the mother.